2022
DOI: 10.3390/molecules27196333
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 5-Chloro-N-phenyl-1H-indole-2-carboxamide Derivative as Brain-Type Glycogen Phosphorylase Inhibitor: Potential Therapeutic Effect on Cerebral Ischemia

Abstract: Brain-type glycogen phosphorylase inhibitors are potential new drugs for treating ischemic brain injury. In our previous study, we reported compound 1 as a novel brain-type glycogen phosphorylase inhibitor with cardioprotective properties. We also found that compound 1 has high blood–brain barrier permeability through the ADMET prediction website. In this study, we deeply analyzed the protective effect of compound 1 on hypoxic-ischemic brain injury, finding that compound 1 could alleviate the hypoxia/reoxygena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…After the successful isolation of mouse astrocytes [ 12 ], we established a H/R injury model and implemented it using an adeno-associated virus (AAV2) to further explore whether compound 1 could act against H/R injury in mouse astrocytes by targeting PYGB. Relevant studies have shown that the degree of H/R injury in mouse astrocytes could be reflected by cell viability, LDH leakage rate, intracellular glucose, and ROS level [ 14 , 15 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After the successful isolation of mouse astrocytes [ 12 ], we established a H/R injury model and implemented it using an adeno-associated virus (AAV2) to further explore whether compound 1 could act against H/R injury in mouse astrocytes by targeting PYGB. Relevant studies have shown that the degree of H/R injury in mouse astrocytes could be reflected by cell viability, LDH leakage rate, intracellular glucose, and ROS level [ 14 , 15 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, ATP is an important energy molecule in cells, and the intracellular ATP content is used to evaluate the level of cellular energy metabolism [ 21 , 22 , 23 , 24 ]. Our previous report showed that compound 1 could dramatically reduce cellular ATP and remarkably improve energy metabolism in mouse astrocytes [ 12 ]. In this study, we wanted to determine ATP content further after PYGB knockdown to validate whether compound 1 worked by targeting PYGB.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations